Newborn physical condition and breastfeeding behaviours: Secondary outcomes of a cluster-randomized trial of prenatal lipid-based nutrient supplements in Bangladesh - Ullah, Md Barkat; Mridha, Malay K; Arnold, Charles D; Matias, Susana L; A Khan, Md Showkat; Siddiqui, Zakia; Hossain, Mokbul; Paul, Rina Rani; Dewey, Kathryn G (Wiley, 2022)
This article was published in Maternal Child Nutrition [ © 2019 John Wiley & Sons Ltd.] and the definite version is available at: https://doi.org/10.1111/mcn.12844. The Journal's website is at: https://onlinelibrary.wiley.com/doi/epdf/10.1111/mcn.12844